Pengaruh Penerapan Akuntansi Pertanggungjawaban, Partisipan Anggaran Dan Job Relevant Information Terhadap Kinerja Manajerial Pada OPD Aceh Tamiang - Fazarila Fazarila; Afrah Junita; Nasrul Kahfi Lubis (LPPM Universitas Labuhanbatu, 2022)
This study aims to determine the Effect of the Application of Accounting For Responsibility, Budget Participants and Job Relevant Information on Managerial Performance at opd Aceh Tamiang. The population of this study is people who are involved in budgeting and understand about the budget in the Aceh Tamiang OPD as many as 32 OPD. The sampling technique uses the Saturated Sample method where all OPDs are sampled. Data collection was carried out by distributing questionnaires to 96 respondents. The data obtained were then analyzed using SPSS (Statistical Package for the Social Sciences). The results showed that simultaneously the variables accounting for accounting, budget participants and job relevant information had a significant influence on managerial performance. While partially showing that the Variable Budget Participants have a significant influence on managerial performance. Meanwhile, the variables of Accountability Accounting and Job Relevant Information have no influence on managerial performance.